Photolysis of Caged-GABA Rapidly Terminates Seizures In Vivo: Concentration and Light Intensity Dependence - Wang, Dan; Yu, Zhixin; Yan, Jiaqing; Xue, Fenqin; Ren, Guoping; Jiang, Chenxi; Wang, Weimin; Piao, Yueshan; Yang, Xiaofeng (Frontiers in Neurology, 2017)
The therapy of focal epilepsy remains unsatisfactory for as many as 25% of patients. The photolysis of caged-γ-aminobutyric acid (caged-GABA) represents a novel and alternative option for the treatment of intractable epilepsy. Our previous experimental results have demonstrated that the use of blue light produced by light-emitting diode to uncage ruthenium-bipyridine-triphenylphosphine-c-GABA (RuBi-GABA) can rapidly terminate paroxysmal seizure activity both in vitro and in vivo. However, the optimal concentration of RuBi-GABA, and the intensity of illumination to abort seizures, remains unknown. The aim of this study was to explore the optimal anti-seizure effects of RuBi-GABA by using implantable fibers to introduce blue light into the neocortex of a 4-aminopyridine-induced acute seizure model in rats. We then investigated the effects of different combinations of RuBi-GABA concentrations and light intensity upon seizure. Our results show that the anti-seizure effect of RuBi-GABA has obvious concentration and light intensity dependence. This is the first example of using an implantable device for the photolysis of RuBi-GABA in the therapy of neocortical seizure, and an optimal combination of RuBi-GABA concentration and light intensity was explored. These results provide important experimental data for future clinical translational studies.